A Single Point Mutation Creating a Furin Cleavage Site in the Spike Protein Renders Porcine Epidemic Diarrhea Coronavirus Trypsin Independent for Cell Entry and Fusion - Li, Wentao (J Virol, 2015)
The emerging porcine epidemic diarrhea virus (PEDV) requires trypsin supplementation to activate its S protein for membrane fusion and virus propagation in cell culture. By substitution of a single amino acid in the S protein, we created a recombinant PEDV with an artificial furin protease cleavage site N terminal of the putative fusion peptide (PEDV-S(FCS)). PEDV-S(FCS) exhibited trypsin-independent cell-cell fusion and was able to replicate in culture cells independently of trypsin, though to low titer.